Modelling the Ultrasonic Diagnosis of Adhesive Bonds - Josko, Marian (Communications - Scientific letters of the University of Zilina, 2007)
In the paper, the conception of modelling the diagnosis of adhesive bonds by ultrasonic method is presented. Two complementary models of bonds diagnosis are presented and discussed. The models proposed reduce an evaluation of coating adherence to assessment of condition of bond between coating and substrate. The models are connected with period of production of adhesive bonds (so called control diagnostic) and with the operational or maintenance period of its existence (operational diagnostic).